(untitled) (Research, Society and Development, 2021)
Small companies lack professionals and strategies with a technical and / or scientific basis, in addition to the fact that in order to act with prominence in the field of training and consulting, they need to have good practices internally. This research aimed to analyze how knowledge management (KM) can contribute to the achievement of sustainability in organizations (SEO). As a methodology, a qualitative approach was used with descriptive and analytical research, of an applied character and cross-sectional perspective, with a single case study strategy, data collection with documentary research and direct observation, applying content analysis. As a main result, it was possible to observe in practice how KM can be used to subsidize an organization along the way to ensure organizational sustainability.